Investigating the effects of gender and scaffolding in developing preschool children’s computational thinking during problem-solving with Bee-Bots - Angeli, Charoula; Georgiou, Kyriakoula (Frontiers in Education, 2023)
The research community has embraced computational thinking as an important skill to develop in school and academic settings. Many researchers argue that computational thinking should be developed in the context of programming and robotic activities in all educational levels of education, starting from early childhood education. Nonetheless, the factors related to the development of computational thinking in pre-school education are still under study, and not too many empirical studies have been conducted to provide empirical evidence about the development of computational thinking in young children. To this end, the present study investigated the effects of scaffolding and gender in developing young children’s computational thinking. The results indicated the main effects of the scaffolds on children’s computational thinking in favor of the children assigned to the experimental groups. Lastly, boys outperformed girls on all occasions, indicating that gender effects exist. The authors conclude that teaching interventions need to be designed in such a way, so they have mathemagenic effects for all learners irrespective of gender. Implications and future research directions are discussed.